2017 IEEE International Conference on Computer Design (ICCD) 2017
DOI: 10.1109/iccd.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Neural Trojans

Abstract: While neural networks demonstrate stronger capabilities in pattern recognition nowadays, they are also becoming larger and deeper. As a result, the effort needed to train a network also increases dramatically. In many cases, it is more practical to use a neural network intellectual property (IP) that an IP vendor has already trained. As we do not know about the training process, there can be security threats in the neural IP: the IP vendor (attacker) may embed hidden malicious functionality, i.e. neural Trojan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
155
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(178 citation statements)
references
References 20 publications
1
155
0
Order By: Relevance
“…In 2017, several concurrent groups explored backdoor attacks in some variant of this threat model. In addition to the three attacks described in detail in Section 2.3 [18,10,27], Muñoz-González et al [34] described a gradient-based method for producing poison data, and Liu et al [28] examine neural trojans on a toy MNIST example and evaluate several mitigation techniques. In the context of the taxonomy given by Barreno et al [7], these backdoor attacks can be classified as causative integrity attacks.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, several concurrent groups explored backdoor attacks in some variant of this threat model. In addition to the three attacks described in detail in Section 2.3 [18,10,27], Muñoz-González et al [34] described a gradient-based method for producing poison data, and Liu et al [28] examine neural trojans on a toy MNIST example and evaluate several mitigation techniques. In the context of the taxonomy given by Barreno et al [7], these backdoor attacks can be classified as causative integrity attacks.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, in their NDSS 2017 paper, Liu et al [27] note that targeted backdoor attacks will disproportionately reduce the accuracy of the model on the targeted class, and suggest that this could be used as a detection technique. Finally, Liu et al's [28] mitigations have only been tested on the MNIST task, which is generally considered unrepresentative of real-world computer vision tasks [46]. Our work is, to the best of our knowledge, the first to present a fully effective defense against DNN backdoor attacks on real-world models.…”
Section: Related Workmentioning
confidence: 99%
“…In terms of defenses, Liu et al [31] only presented some brief intuitions on backdoor detection, while Chen et al [13] reported a number of ideas that are shown to be ineffective. Liu et al [32] proposed three defenses: input anomaly detection, re-training, and input preprocessing, and require the poisoned training data. A more recent work [49] leveraged trace in the spectrum of the covariance of a feature representation to detect backdoor.…”
Section: Related Workmentioning
confidence: 99%
“…Works in [32], [33] suggest approaches to remove the trojan behavior without first checking whether the model is trojaned or not. Fine-tuning is used to remove potential trojans by pruning carefully chosen parameters of the DNN model [32].…”
Section: B Defensesmentioning
confidence: 99%
“…It is also cumbersome to perform removal operations to any DNN model under deployment as most of them tend to be benign. Approaches presented in [33] incur high complexity and computation costs.…”
Section: B Defensesmentioning
confidence: 99%